Carbon Backbone Topology of the Metabolome of a Cell - Bingol, Kerem (2012)
The complex metabolic makeup of a biological system, such as a cell, is a key determinant of its biological state providing unique insights into its function. Here we characterize the metabolome of a cell by a novel homonuclear (13)C 2D NMR approach applied to a non-fractionated uniformly (13)C-enriched lysate of E. coli cells and determine de novo their carbon backbone topologies that constitute the ‘topolome’. A protocol was developed, which first identifies traces in a constant-time (13)C-(13)C TOCSY NMR spectrum that are unique for individual mixture components and then assembles for each trace the corresponding carbon-bond topology network by consensus clustering. This led to the determination of 112 topologies of unique metabolites from a single sample. The topolome is dominated by carbon topologies of carbohydrates (34.8%) and amino acids (45.5%) that can constitute building blocks of more complex structures.